Tracking the hydro-climatic signal from lake to sediment: a field study from central Turkey - Dean, Jonathan R. (Elsevier, 2015)
Palaeo-hydrological interpretations of lake sediment proxies can benefit from a robust understanding of the modern lake environment. In this study, we use Nar Gölü, a non-outlet, monomictic maar lake in central Turkey, as a field site for a natural experiment using observations and measurements over a 17-year monitoring period (1997–2014). We compare lake water and sediment trap data to isotopic, chemical and biotic proxies preserved in its varved sediments. Nar Gölü underwent a 3 m lake-level fall between 2000 and 2010. δ18Olakewater is correlated with this lake-level fall, responding to the change in water balance. Endogenic carbonate is shown to precipitate in isotopic equilibrium with lake water and there is a strong relationship between δ18Olakewater and δ18Ocarbonate, which suggests the water balance signal is accurately recorded in the sediment isotope record. Over the same period, sedimentary diatom assemblages also responded, and conductivity inferred from diatoms showed a rise. Shifts in carbonate mineralogy and elemental chemistry in the sediment record through this decade were also recorded. Intra-annual changes in δ18Olakewater and lake water chemistry are used to demonstrate the seasonal variability of the system and the influence this may have on the interpretation of δ18Ocarbonate. We use these relationships to help interpret the sedimentary record of changing lake hydrology over the last 1725 years. Nar Gölü has provided an opportunity to test critically the chain of connection from present to past, and its sedimentary record offers an archive of decadal- to centennial-scale hydro-climatic change